FIGURE 28 in A small collection of rare and new chitons (Mollusca: Polyplacophora) from the Tasmanian Museum and Art Gallery ... - Sirenko, Boris (Zenodo, 2023)
FIGURE 28. Stenosemus simplicissimus, Southern Ocean, Heard Island, (TMAG, E 26179), BL 20.0 mm: A, B, D. Dorsal corpuscles, ventral scales and marginal spicules and bristles; C. Dorsal corpuscles and ventral spicules ... : Published as part of Sirenko, Boris, 2023, A small collection of rare and new chitons (Mollusca: Polyplacophora) from the Tasmanian Museum and Art Gallery, pp. 359-392 in Zootaxa 5325 (3) on page 383, DOI: 10.11646/zootaxa.5325.3.3, http://zenodo.org/record/8247001 ...